Safety, Pharmacokinetics/Pharmacodynamics, and Absolute Bioavailability of Dexmedetomidine Hydrochloride Nasal Spray in Healthy Subjects: A Randomized, Parallel, Escalating Dose Study - Kuang, Yun; Wang, Sai-Ying; Wang, Meng-Na; Yang, Guo-Ping; Guo, Can; Yang, Shuang; Zhang, Xing-Fei; Yang, Xiao-Yan; Pei, Qi; Zou, Chan; He, Yan-Hong; Zhou, Ying-Yong; et al. (Frontiers in Pharmacology, 2022)
Background The study evaluated the safety, pharmacokinetics/pharmacodynamics (PK/PD) and absolute bioavailability (Fabs) of Dex nasal spray in healthy adult subjects, which serves as a bridge for subsequent study in children. Methods Part 1, a double-blind, placebo-controlled, single ascending dose study was performed with 48 subjects. For 20-/40-μg groups, every 6/2 subjects received either Dex/placebo nasal spray or Dex/placebo injection in two periods. 12/4 subjects received 100μg Dex/placebo nasal spray. Part 2, a randomized, double-blind, placebo-controlled study, 12/4 subjects received 150μg Dex/placebo nasal spray. Part 3, a randomized, open, self-crossover study. 12 subjects received 20μg or 100μg Dex nasal spray in two periods alternately. The method of administration was optimized in part 2 and part 3. Results In part 1, Dex nasal spray was well-tolerated up to the maximum dose of 100μg, the Fabs was only 28.9%-32.3%. Part 2 and part 3 adopt the optimized nasal spray method to promote Fabs of Dex nasal spray to 74.1%-89.0%. A severe adverse event was found in part 2. 100μg in part 3, the Ramsay score increased the most and lasted the longest and the BIS score decreased most significantly. Conclusion Using the optimized nasal spray method, a single dose of 20/100μg of the test drug was safe and tolerable, and 100μg may have approached or reached the plateau of sedation. In addition, the optimized method can greatly improve the bioavailability of the test drug and has more reference value. Trial registration number: ChiCTR-IIR-17013180 and ChiCTR1900026141